Multifunctional Mitochondria-Targeting Nanosystems for Enhanced Anticancer Efficacy - Hu, Tingting; Qin, Zhou; Shen, Chao; Gong, Han-Lin; He, Zhi-Yao (Frontiers in Bioengineering and Biotechnology, 2021)
Mitochondria, a kind of subcellular organelle, play crucial roles in cancer cells as an energy source and as a generator of reactive substrates, which are regarding to the generation, proliferation, drug resistance and other functions of cancer. Therefore, precise delivery of anticancer agents to mitochondria can be a novel strategy for enhanced cancer treatment. Mitochondria have a four-layer structure with high negative potential, which thereby prevent many molecules from reaching the mitochondria. Luckily, the advances in nanosystems have provided enormous hope to overcome this challenge. These nanosystems include liposomes, nanoparticles, nanomicelles, etc. Here, we summarize the very latest developments of mitochondria-targeting nanomedicines in cancer treatment as well as focus on designing multifunctional mitochondria-targeting nanosystems based on the latest nanotechnology.